EVALUATING THE EFFECT OF INFORMATION TECHNOLOGY ON THE FIRM’S SUPPLY CHAIN COLLABORATION IN MALAYSIA –EXAMINING MODERATING ROLE OF ASSOCIATION AMONG PARTNERS - Muhammad Raza,Dr. Ali Alshebami,Dr. Atif Aziz (International Journal of Advanced Science and Technology, 2020)
Purpose: The main objective of the study is to investigate the effect of information technology on the supply chain collaboration in Malaysia while examining the moderating role of association among partners.